Simulation of floor response spectra in shake table experiments. - Maddaloni, G. (Earthquake engineering & structural dynamics.)
Among several different experimental techniques, used to test the response of structures and to verify their seismic performance, the shake table testing allows to reproduce the conditions of true effects of earthquake ground motions in order to challenge complex model structures and systems. However, the reproduction of dynamic signals, due to the dynamics of the shake table and of the specimen, is usually imperfect even though closed-loop control in a shake table system is used to reduce these errors and obtain the best fidelity reproduction. Furthermore, because of the dynamic amplifications in the specimen, the signal recorded at desired locations could be completely different from the expected effect of shake table motion. This paper focuses on the development of practical shake table simulations using additional ?open loop? feedforward compensation in form of inverse transfer functions (i.e. the ratio of the output structural response to an input base motion in the frequency domain) in order to obtain an acceptable reproduction of desired acceleration histories at specific locations in the specimen. As the first step, a well-known global feedforward procedure is reformulated for the compensation of the table motion distortions due to the servo-hydraulic system. Subsequently, the same concept is extended to the table-structure system to adjust the shake table input in order to achieve a desired response spectrum at any floor of the specimen. Implementations show how such a method can be used in any experimental facility.